Ship’s de-perming process using coils lying on seabed - Mirosław Wołoszyn; Piotr Jankowski (Metrology and Measurement Systems, 2019)
A ship built from ferromagnetic steel disturbs the uniformity of the Earth’s magnetic field. Changes of ship’s signature are due to the magneto-mechanical interaction of the hull with the Earth’s magnetic field. The ship’s magnetic field can be detected by a magnetic naval mine. For this reason, the vessel has to be demagnetized. There are several methods of ship’s de-perming. The results of experimental and computer simulations of the ship’s de-perming process using coils lying on the seabed are presented in this paper. The simulation of the de-perming process with a hysteresis model of ship’s steel was carried out in Opera-3d 18R2. The laboratory experiments were carried out using a physical ship’s model, several Helmholtz coils, magneto-resistive sensors, etc. The experiments and computer simulations have shown that ship’s de-perming with coils lying on the seabed is possible. The values of coil currents are over dozen times greater than those used in the standard method.